PHONOLOGICAL INTERFERENCE OF JAVANESE AND INDONESIAN VOWELS IN THE FOREIGN LANGUAGE ACQUISITION OF ENGLISH VOWEL /ɑ/ - Inayah, Nella Alfian; Fajri, Anisah Durrotul; Saffanatussa'idiyah (Faculty of Letters Universitas Balikpapan, 2026)
English has been regarded as a foreign language taught in formal schools as part of the national curriculum in Indonesia. This position has made English come into contact with local and national language as most Indonesians speak more than one language. Given the multilingual environment, examining phonological interference may address difficulties and possibly offer insight on the possibility of formulating pronunciation learning models. This research examines the phonological interference of Javanese (L1) and Bahasa Indonesia (L2) on English vowels /ɑ/ . Qualitative research design was administered to conduct the study with observation as data collection technique complemented with field notes on the realization of phoneme. Interactive model analysis was then used to analyze the phonological interference and the factors influencing it based on the phoneme realization. The findings indicate that the production of the English vowel /ɑ/ is greatly influenced by both Javanese and Bahasa Indonesia. Phonological interference involved actual phone substitution to vowel /o/, /ɔ/, and /a/ occured at the beginning of the word while substitution to vowels /o/, /ə/, /a/, and diphthong /aʊ happened in the middle. Substitutions in the two positions occured because of the orthographic factors and different phonemic systems in L1 and L2 with English.